Proceso de atención enfermería en paciente de 54 años con enfermedades crónicas degenerativas. - Zambrano Guerrero, Yuslady Belén (2023)
Diabetes, renal failure and thrombocytopenia are chronic degenerative diseases that affect the entire population in general, since it has been a worldwide problem according to the WHO World Health Organization, if these diseases are not treated in time it could cause the death of the human being. These diseases have been affecting the whole world for many years, but in recent times it has become evident that there is a higher percentage of people who suffer from these pathologies, it has become a major problem due to lack of knowledge, due to the sedentary lifestyle and poor diet that people have today. Diabetes is a disease that seriously affects Ecuador, being the third cause of death in the country, arterial hypertension refers to a picture of high pressure, generally this pathology does not present any symptoms for many years (until it causes an injury in a vital organ). Renal failure is defined as the decreased ability of the kidneys to excrete nitrogenous waste, established over hours or days. While thrombocytopenia is a condition that appears when the blood platelet count is too low. Through which the nursing care process was applied systematically with the help of the NANDA, NOC and NIC taxonomy to use the nursing diagnosis and then be able to implement the care plan for the improvement of their health.